Individual Taxpayer Compliance In Jakarta, Indonesia - Putri, Wulan Aulia; Pratiwi, Monica Weni (Journal of International Conference Proceedings, 2022)
The purpose of this study is to examine the effect of tax socialization on individual taxpayer compliance, which is moderated by taxpayer awareness and understanding of taxation. The topic of individual taxpayer compliance is an interesting one to study because it looks at it from two perspectives, namely strength and trust in authorities. There are also differences in results from previous studies, which motivates the research. This study tries to analyse the effect of tax socialization on individual taxpayer compliance, which is mediation by taxpayer awareness and understanding of taxation. The sampling technique used in this study was probability sampling, namely simple random sampling. The sample size in this study was 111 respondents. According to the findings of the study, tax socialization has an effect on individual taxpayer compliance, which is mediation by taxpayer awareness. Based on the research results, further research can add service quality variables. Good service quality will have an impact on increasing individual taxpayer compliance in carrying out their tax obligations, and then providing quality services to taxpayers will make taxpayers further increase individual taxpayer compliance in fulfilling their tax obligations.Keywords: Individual Taxpayer Compliance, Strength and Trust in Authorities, Tax Socialization, Taxpayer Awarennes, and Understanding of Taxation.